The Significance of the Council of Trent - Wright, A. D. (The journal of ecclesiastical history, 1975)
The emotive associations of the epithet Tridentine reveal confusion over the Council of Trent, which has continued from the seventeenth century to the present day. The complaints of Sarpi, the attacks of Leibnitz, the apologia of Bossuet, the abuse of Protestants, and the recriminations of modern Catholics all reveal different views of the Council's nature, its intentions and its achievements. Implicit in all views, however, is the concept of a Council which had lasting effects.